Pengaruh Kualitas Pelayanan Bank Syariah terhadap Kepuasan Mahasiswa Universitas Sains Islam Al Mawaddah Warrahmah Kolaka Sebagai Nasabah Bank Syariah: Studi Kasus di BSI Cabang Kolaka - Hasniar Hasniar; Malika Kesya Aulia; Herni Herni; Sulkifli A R (AKUNTANSI 45, 2025)
This study aims to examine the influence of Islamic bank service quality on the satisfaction level of students at Universitas Sains Islam Al Mawaddah Warrahmah Kolaka who are customers of BSI (Bank Syariah Indonesia) Kolaka Branch. In Islamic banking, service quality plays a pivotal role in fostering customer satisfaction and loyalty, especially among students who are more critical of service experiences. A quantitative method was applied using a survey approach, distributing questionnaires to student users of BSI services. Data were analyzed through simple linear regression using SPSS software. The results reveal a significant and positive influence between service quality and student satisfaction. The coefficient of determination (R²) is 0.652, indicating that 65.2% of the variance in satisfaction is explained by service quality. Therefore, improvements in various service aspects including efficiency, hospitality, clarity of information, and physical facilities greatly enhance student satisfaction. The study recommends improving staff competence, providing student-friendly facilities, and optimizing service-related information to be clearer and more accessible.